'Bringing the state back in': A political economy analysis of Portuguese immigration policy. Issue 4 (2nd October 2018) - Carvalho, João
Abstract: Southern European states are recurrently represented as 'safe havens' for irregular immigration in face of powerless national governments. Drawing from an interdisciplinary approach combining the domestic politics approach and the political economy of migration, this investigation explores the effectiveness of the Portuguese policy towards labour and irregular inflows during the 1990s and the 2000s. Against the increasing exclusion of politics and national governments in immigration studies, this research focuses on the agency of the Portuguese state. This article associates the intensity of irregular inflows with the covert expansive approach towards immigration adopted by the Portuguese state, driven by economic objectives.